Square-Planar Pt(II) and Ir(I) Complexes as the Lewis Bases: Donor-Acceptor Adducts with Group 13 Trihalides and Trihydrides - Chval, Zdeněk; Dvořáčková, Olga; Chvalová, Daniela; Burda, Jaroslav V (Inorganic chemistry, 2019)
The stability and properties of donor-acceptor adducts of square-planar Pt(II) and Ir(I) complexes (designated as PtX, IrX, or generally MX complexes) with trihydrides and trihalides of group 13 elements of general formula YZ3 (Y = B, Al, Ga; Z = H, F, Cl, Br) were studied theoretically using DFT methodology in the gas phase. MX complexes were represented by wide range of the ligand environment which included model complexes [Ir(NH3)3X]0 and cis-[Pt(NH3)2X2]0 (X = H, CH3, F, Cl, Br) and isoelectronic complexes [Ir(NNN)(CH3)]0 and [Pt(NCN)(CH3)]0 with tridentate NNN and NCN pincer ligands. MX complexes acted as the Lewis bases donating electron density from the doubly occupied 5d z2 atomic orbital of the metal M atom to the empty valence p z orbital of Y whose evidence was clearly provided by the natural atomic orbital (NAO) analysis. This charge transfer led to the formation of pentacoordinated square pyramidal MX·(YZ3) adducts with M·Y dative bond. Binding energies were -44.7 and -75.2 kcal/mol for interaction of GaF3 as the strongest acid with PtNCN and IrNNN pincer ligands complexes. Only M·B bonds had covalent character although MX·BZ3 adducts were the least stable due to large values of Pauli repulsion and deformation energies. The highest degree of covalent character was found for adducts of BH3 in all series of structures studied. Al and Ga adducts showed remarkably similar behavior with respect to geometry and binding energies.